UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETIL ASETAT DAUN AJERAN (Bidens pilosa L.) TERHADAP BAKTERI Staphylococcus aureus - Nufus, Hayatun; Kusumawati, Kurnia; Theresia Ka, Rori; Pratiw, Afifah (Jurnal Nusantara Madani, 2024)
Background:Staphylococcus aureus bacteria is the one of the causes of acne. Ajeran leaves contain flavonoid, saponin, and fenol compounds which have the potential to have antibacterial activity. The purpose of this study was to determine whether the ethyl acetate extract of ajeran leaves (Bidens pilosa L.) has antibacterial activity against Staphylococcus aureus and to determine the concentration that inhibits the growth of Staphylococcus aureus bacteria. Subjects and methods:This research is anexperimental research. The research phase began with the extraction of ethyl acetate form ajeran leaves (Bidens pilosa L.) using the maceration method. Antibacterial activity was tested using the disc diffusion method and the dilution method, with extract concentrations of 200 ppm, 400 ppm, 600 ppm, 800 ppm, 1000 ppm. Results:Measurement results of the inhibition zone of ethyl acetate extraction of ajeran leaves (Bidens pilosa L.) with extract concentrations of 200 ppm, 400 ppm, 600 ppm, 800 ppm, 1000 ppm against Staphylococcus aureus 6.33 mm, 4.33 mm, 5 mm, 6 mm and 3 mm in the very weak category. Good concentration results at the minimum inhibitory concentration (MIC) dilution method with a concentration of 200 ppm.Conclusion:Ethyl acetate extract of ajeran leaves (Bidens Pilosa L.) has antibacterial activity against Staphylococcus aureus bacteria.